2022
DOI: 10.1142/s1793292022500448
|View full text |Cite
|
Sign up to set email alerts
|

Nanoarchitectonics of Sn3O4/g-C3N4 Heterostructure Materials for Better Photocatalytic and Electrochemical Performance

Abstract: Sn3O4/g-C3N4 heterostructure nanomaterials were prepared by calcining melamine and the hydrothermal method. The microstructure and morphology of the synthesized specimen were characterized by X-ray diffraction (XRD), electron microscope (SEM and TEM) and nitrogen adsorption and desorption (BET). The photocatalytic activity was evaluated by the photodegradation of methylene blue (MB) under visible light irradiation and the electrochemical performance was tested under a typical three-electrode configuration. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This approach capitalizes on both Faradaic and non-Faradaic reactions of electron transport, facilitating further effective charge transfer within the composite. Notably, Hu et al 31 demonstrated that a Sn 3 O 4 -decorated g-C 3 N 4 nanostructure exhibited a 28.6% increase in electrochemical activity (Cs = 648 F/g @ 1 A/g) compared to Sn 3 O 4 alone, attributed to the formation of a heterojunction. Similarly, Shi et al 32 achieved a hybrid structure by combining g-C 3 N 4 with a beta-Ni(OH) 2 flow-like structure through a simple hydrothermal method.…”
mentioning
confidence: 99%
“…This approach capitalizes on both Faradaic and non-Faradaic reactions of electron transport, facilitating further effective charge transfer within the composite. Notably, Hu et al 31 demonstrated that a Sn 3 O 4 -decorated g-C 3 N 4 nanostructure exhibited a 28.6% increase in electrochemical activity (Cs = 648 F/g @ 1 A/g) compared to Sn 3 O 4 alone, attributed to the formation of a heterojunction. Similarly, Shi et al 32 achieved a hybrid structure by combining g-C 3 N 4 with a beta-Ni(OH) 2 flow-like structure through a simple hydrothermal method.…”
mentioning
confidence: 99%